Additionality in Grassland Easements to Provide Migratory Bird Habitat in the Northern Plains - Roger Claassen; Jeff Savage; Chuck Loesch; Vince Breneman; Ryan Williams; Bill Mulvaney; Tammy Fairbanks (Journal of Agricultural and Resource Economics, 2017)
Native grassland in the Prairie Pothole Region (PPR) is important habitat for migratory birds, particularly ducks. Much of this grassland is at risk for conversion to cropland. Permanent easements, managed by the U.S. Fish and Wildlife Service, protect high-quality habitat but do not currently consider vulnerability to cropland conversion. We find that (i) grassland easements are protecting native grassland from conversion, although the level of protection is modest; (ii) it may be possible to increase habitat protection by targeting grassland that is vulnerable to cropland conversion; and (iii) conversion estimates that fail to account for easements are biased downward.